Ethics, psychiatry and mental health - Perales, Alberto (Acta Bioethica, 2016)
After delimiting the concepts of moral and ethics the author makes a conceptual difference between psychiatry and mental health. He proposes that the former is a medical specialty while the latter is built in the health concept. Psychiatric problems correspond to mental disorders that affect individual persons while mental health problems, such as underdevelopment and poverty, generalized corruption and violence affect the whole society and interfere with human development and economic growth. To mix up both concepts as if they were synonymous, especially in third world countries, leads to scientific, economic and socio-political risks that attempt against their developments as nations.